2003
DOI: 10.3141/1840-08
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Crash Prediction Model for Application to Crash Prevention in Freeway Traffic

Abstract: The likelihood of a crash or crash potential is significantly affected by the short-term turbulence of traffic flow. For this reason, crash potential must be estimated on a real-time basis by monitoring the current traffic condition. In this regard, a probabilistic real-time crash prediction model relating crash potential to various traffic flow characteristics that lead to crash occurrence, or “crash precursors,” was developed. In the development of the previous model, however, several assumptions were made t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
107
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 240 publications
(109 citation statements)
references
References 5 publications
(4 reference statements)
2
107
0
Order By: Relevance
“…Since the values of the log-likelihood ratio χ 2 were found to be low with p-values close to 1 in all cases, the model fit was adequately high at a 95% confidence level (α = 0.05). This modified model displayed slightly better performance than the model we developed in the previous study (6). As expected, high-level crash precursors generally contribute to high crash frequency.…”
Section: Crash Prediction Modelmentioning
confidence: 62%
See 1 more Smart Citation
“…Since the values of the log-likelihood ratio χ 2 were found to be low with p-values close to 1 in all cases, the model fit was adequately high at a 95% confidence level (α = 0.05). This modified model displayed slightly better performance than the model we developed in the previous study (6). As expected, high-level crash precursors generally contribute to high crash frequency.…”
Section: Crash Prediction Modelmentioning
confidence: 62%
“…In our previous studies (5,6), the following three crash precursor variables were identified: (1) the coefficient of variation of speed (which is equal to the standard deviation of speed divided by the average speed) upstream of a specific location (CVS), (2) average density (D), and (3) average speed difference between the upstream and downstream of a specific location (Q). The details of model structure, the calculation of precursors including the determination of observation time slice duration (time offset), the categorization of precursor variables, and the calibration of parameters using real traffic data are discussed in Lee et al (5,6). …”
Section: Crash Prediction Modelmentioning
confidence: 99%
“…) was modified in 2003 [15], and then in 2004 [16] by the author and implemented in the simulation of a smaller transport network, 2.5 km long, which contains four inductive loops, three variable message signs and three traffic lanes. As a conclusion of the said simulation, the obtained results show that the average crash potential is reduced by approximately 25% by using the system of variable traffic signs and the crash prevention model.…”
Section: Overview Of Previous Researchmentioning
confidence: 99%
“…The United States and Canada began to carry out researches on the traffic accident detection algorithms and the traffic flow harbinger characteristics before the traffic accident from 1990s [8][9][10][11][12][13][14][15]. Among them, Chris adopted the speed differences between upstream and downstream, and the variances of the cross-section speed as the characterization factors of the traffic flow real-time risk discrimination [9], the results of which was referenced by Kansas state highway agency of USA in 2006.…”
Section: Introductionmentioning
confidence: 99%